Long‐Term Statin Use Is Associated With Reduced Rates of Adverse Events in Patients With Newly Diagnosed Atrial Fibrillation - Huang, Ting‐Chun; Yap, Li‐Hao; Chen, Chao‐Yu; Lin, Hui‐Wen; Lin, Sheng‐Hsiang; Li, Yi‐Heng (Journal of the American Heart Association, 2024)
The effectiveness of statin use in preventing adverse cardiovascular events in individuals with atrial fibrillation (AF) has remained uncertain. This study aimed to assess whether statin use could lead to better outcomes among individuals with AF. We enrolled 397 787 patients with AF from January 1, 2012 to December 31, 2020. Patients with AF were divided into 2 groups (statin user and statin nonuser), and the risks of composite outcomes (including ischemic stroke, hemorrhagic stroke, and transient ischemic attack), all-cause death, and major adverse cardiovascular events (which encompassed cardiovascular death, myocardial infarction, stroke, and heart failure hospitalization) were analyzed. We analyzed 288 958 patients with newly diagnosed AF (mean age, 73 years; 44% women; mean CHA DS -VASc score, 3.5). Compared with patients without statin use, statin users had lower risks of composite end points (adjusted hazard ratio [HR], 0.91 [95% CI, 0.87-0.94]; <0.01). In regard to all-cause death, statin users exhibited a 67% risk reduction compared with statin nonusers (adjusted HR, 0.33 [95% CI, 0.32-0.33]; <0.01). Statin use was also associated with reduced incidence of major adverse cardiovascular events (adjusted HR, 0.64 [95% CI, 0.63-0.66]; <0.01). In the subgroups stratified by CHA DS -VASc score, statin therapy was particularly effective for patients with CHA DS -VASc scores 0 to 3 for composite end points but consistently reduced all-cause mortality and major adverse cardiovascular events across all score categories. Among patients with newly diagnosed AF, statin use was associated with lower risk of ischemic stroke, hemorrhagic stroke, transient ischemic attack, all-cause mortality, and major adverse cardiovascular events.